2020
DOI: 10.1097/dss.0000000000002112
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Triamcinolone May Not Be Beneficial for Treating Acute Hidradenitis Suppurativa Lesions: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: BACKGROUND Hidradenitis suppurativa (HS) is a chronic, inflammatory condition characterized by recurrent nodules, sinus tracts, comedones, and scarring. Hidradenitis suppurativa is often associated with pain and decreased quality of life. Limited clinical trial data exist regarding the management of acute HS lesions, but clinical experience and a prospective case series suggest that intralesional triamcinolone may be useful.OBJECTIVE To compare the efficacy of intralesional triamcinolone to placebo for the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
0
32
1
1
Order By: Relevance
“…They did not find any difference in the number of days for lesion resolution, or any change in pain or patient-reported severity between the different tails of the study. We consider that this low effectiveness is due to an insufficient (0.1 ml) dose of corticosteroid and because the infiltrations were not assisted by ultrasonography 18 .…”
Section: Discussionmentioning
confidence: 99%
“…They did not find any difference in the number of days for lesion resolution, or any change in pain or patient-reported severity between the different tails of the study. We consider that this low effectiveness is due to an insufficient (0.1 ml) dose of corticosteroid and because the infiltrations were not assisted by ultrasonography 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In an uncontrolled prospective case series, Riis et al 10 reported decreased erythema, edema, suppuration, lesion size, and pain in 36 patients using a single dose of ILTAC‐10 for acute HS flares. Earlier studies of high‐dose ILTAC therapy had contradictory conclusions, but widespread variations in study design may explain these differences 9,12 …”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Recently, some authors described the efficacy of intralesional corticosteroid injection for the treatment of HS [10][11][12][13] while a placebocontrolled trial showed no statistically significant difference between triamcinolone and placebo infiltrated in 67 lesions of 32 HS patients. 14 Limitations of our study are the small sample size, the singlecenter study design, and the short follow-up period for clinical and QoL evaluation. A further limitation is the lack of a control group, for example, corticosteroids or antibiotics alone.…”
Section: Resultsmentioning
confidence: 97%
“…8 Intralesional injection of corticosteroids has been utilized for the treatment of inflammatory lesions of HS in a few case-series studies, in a placebo-controlled trial and it is mentioned in guidelines based on expert consensus. 1,[9][10][11][12][13][14] In particular, in 2016 Riis et al 10 reported 33 cases of HS in which nodular and abscess lesions were treated with intralesional infiltrations of triamcinolone with a significant reduction in lesion erythema, edema, suppuration, and size. Furthermore, a Canadian group reported the infiltration of corticosteroids in a third of their HS patients to successfully manage acute flare-ups of the disease and to reduce the use of systemic antibiotics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation